2021
DOI: 10.1111/csp2.437
|View full text |Cite
|
Sign up to set email alerts
|

Habitat loss accelerates for the endangered woodland caribou in western Canada

Abstract: Habitat loss is often the ultimate cause of species endangerment and is also a leading factor inhibiting species recovery. For this reason, species‐at‐risk legislation, policies and plans typically focus on habitat conservation and restoration as mechanisms for recovery. To assess the effectiveness of these instruments in decelerating habitat loss, we evaluated spatiotemporal habitat changes for an iconic endangered species, woodland caribou (Rangifer tarandus caribou). We quantified changes in forest cover, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 64 publications
2
65
3
Order By: Relevance
“…Instead, conservation biologists try to tackle present‐day problems threatening populations. Put bluntly, why worry about future melting permafrost if woodland caribou Rangifer tarandus population size is declining due to timber harvesting removing vital habitat (Nagy‐Reis et al., 2021), or worry about the genetic recovery of future black rhinoceros Diceros bicornis populations when poaching reduced their global population by 95% in three decades (Berger, 1994). Far too many species will count themselves lucky to run the gamut of climate change if they manage to survive more urgent and direct impacts on their viability.…”
Section: Why the Emphasis On Climate Change?mentioning
confidence: 99%
“…Instead, conservation biologists try to tackle present‐day problems threatening populations. Put bluntly, why worry about future melting permafrost if woodland caribou Rangifer tarandus population size is declining due to timber harvesting removing vital habitat (Nagy‐Reis et al., 2021), or worry about the genetic recovery of future black rhinoceros Diceros bicornis populations when poaching reduced their global population by 95% in three decades (Berger, 1994). Far too many species will count themselves lucky to run the gamut of climate change if they manage to survive more urgent and direct impacts on their viability.…”
Section: Why the Emphasis On Climate Change?mentioning
confidence: 99%
“…We defined the historical forestry disturbance‐caribou abundance relationship of SGSMC using best available abundance data and a simulation model to estimate spatial‐temporal timber harvest and road development. This novel approach is useful for filling disturbance data gaps (specifically, the timing of haul road development) and provides an alternative to using satellite imagery (Johnson et al 2020, Nagy‐Reis et al 2021). Using our approach, we reject our first hypothesis that caribou abundance is most negatively related to forestry disturbances in core habitat.…”
Section: Discussionmentioning
confidence: 99%
“…The southern group of the southern mountain population of woodland caribou (SGSMC; Environment Canada 2014) is an ecologically distinct group that has experienced an estimated 50% loss in habitat and several subpopulation extirpations (Wittmer et al 2010, Festa-Bianchet et al 2011. Habitat management to conserve these caribou has largely prioritized protection of areas occupied by caribou (i.e., core habitat); however, there is increasing evidence that these efforts may be insufficient to support stable caribou populations (Wittmer et al 2007(Wittmer et al , 2010Nagy-Reis et al 2021). Apps et al (2013) concluded that habitat conditions outside of core southern mountain population habitats can drive numerical and functional predator responses, suggesting that habitat management strategies are also needed for matrix habitats (i.e., habitats adjacent to core habitats).…”
mentioning
confidence: 99%
“…By the time managers turn to predator reduction as a means to reverse the decline of caribou populations, multiple warning signals have already flashed. Even with mounting empirical evidence that confirms a relationship between habitat loss and population decline, industrial disturbance has accelerated over the past several decades since caribou declines were first documented (Environment Canada, 2012;Johnson et al, 2015Johnson et al, , 2020Nagy-Reis et al, 2021;Rempel et al, 2021;Rudolph et al, 2017). Governments have relied on piecemeal mitigation of impacts, rather than limitation of the industrial footprint, long after caribou were legally recognized as Threatened or Endangered.…”
Section: Ethical Philosophical and Social Dimensions Of Predator Mana...mentioning
confidence: 99%